The Teaching Of English In Superior Science Classes The Congruence Of Students’ Needs And Program Goals - Susanah Susanah (JAMBI-ENGLISH LANGUAGE TEACHING, 2017)
English is mandatoryfor students of Superior Science Program of teacher education (PGMIPA-U) in the Faculty of Teacher Training and Education of Jambi University because science courses are expected to be taught bilingually through English and Bahasa Indonesia. Therefore, English is a must-to-achieve for students enrolled in this program. This paper focuses on identifying what the students need to achieve in the courses of Englishas EFL and EAP as well as what the program really wants the students to gain through the courses. Moreover, the paper pinpoints whether the students’ needs are congruent with the program goals. Data were taken through a questionnaire, interview with thechief of the program, Group interview with 10 students from Physics Teacher education, and program documents. The findings of this study reveal that students’ needs and program goals are aligned for developing general and discipline-related communicative practices. The Teaching of EFL course is centered on general communicative skills supported with proper linguistic knowledge. Meanwhile EAP courses are structured hierarchal which begins with constructing reading comprehension on subject-related texts to build students’ competence of writing academic compositions related to their discipline and ends in students’ pedagogic competence of teaching science in English.